Ownership Structure and Financial Performance of Companies in Uganda - Sunday, Arthur; Turyahebwa, Abanis; Mabonga, Erick; Byamukama, Eliab; Tukei, Martin (Journal for Studies in Management and Planning, 2017)
This study investigated the effects of change in ownership structure on financial performance of privatized companies in Uganda for the period 2010-2016. The study was informed by the property rights, the agency and the resource based theories. Data was extracted from prospectuses and financial reports of privatized companies, obtained from the Capital Markets Authority and the Uganda Stock Exchange. A unit root test was used to examine stationality of data while a Hausman test determined the appropriate regression model. This study used a Fixed Effects (FE) regression model with a robust standard error option to control for heteroskedasticity and contemporaneous correlation which may lead to spurious results. The study found that ownership structure has a significant relationship with financial performance. Among individual variables, government ownership has a positive influence on ROA and the Tobin’s Q; but a negative effect on cost efficiency. Institutional shareholders have a positive influence on ROA and technical efficiency. Large individual investors have a positive influence on cost efficiency while dispersed shareholders have a positive influence on ROA but a negative effect on cost efficiency. In view of these findings, this study recommends that the Privatization Sector of Uganda should restructure ownership structure of privatized companies to reduce government and dispersed ownership further to pass more control to private investors. However, the government should retain some ownership in privatized firms to enhance shareholders confidence, protection of investments and managerial monitoring. A strategic institutional investor in each company should be identified and be allocated adequate ownership to enable privatized companies to attract managerial and technical expertise crucial to improve governance and financial performance.
Keywords: Privatization; Ownership structure; Financial Performance